Bad News: An Experimental Study on the Informational Effects Of Rewards - Bremzen, Andrei; Khokhlova, Elena; Suvorov, Anton; van de Ven, Jeroen (The Review of Economics and Statistics, 2015)
Psychologists and economists have argued that rewards often have hidden costs. One possible reason is that the principal may have incentives to offer higher rewards when she knows the task is difficult. Our experiment tests if high rewards embody such bad news and if this is correctly perceived by their recipients. Our design allows us to decompose the overall effect of rewards on effort into a direct incentive and an informational effect. The results show that participants correctly interpret high rewards as bad news. In accordance with theory, the negative informational effect coexists with the direct positive effect.